Drought Analysis from Incident Rainfall and Excess Deficit Rainfall at Ootacamund (India) - Das, D.C.; Raghunath, B; Chandrasekhar, K.; Thomas, P.K. (Journal of Soil and Water Conservation, 2022)
The Nilgiris in general, with two monsoons and luxuriant evergreen vegetation, do not appear to have any drought hazard. in the memoirs of the Department of Agriculture, Madras (1) and the Madras Statistical Atlas (2) no such mention has been made. However in the recent years, the shortage of water has been felt by the residents and it has affected the agricultural production. The land revenue dues during 1969 were waived by the Government, considering failure of crop and persisting low rainfall over preceeding years (3). Drought is a relative term that varies with purpose and time (10). There is increasing demand for larger volume of water. Ootacamund receives an average annual rainfall of 130 cms. (5) against the district average of 181 cms. This paper, therefore, examines the available rainfall record to find out if the place had been subject to any drought hazard in the past and the probability of recurrence of such conditions.